Homogenization of Macroinvertebrate Assemblages and Asiatic Clam Corbicula fluminea Invasion in a River of the Arid Patagonian Plateau, Argentina - Labaut, Yeny (2021)
Fil: Labaut, Yeny. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.